Pengaruh Corporate Image Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada PT POS Indonesia (Persero) Kantor Pos Cimahi - Wulan Yuliyana; Cici Rengganis; Adi Suparwo (Jurnal Wira Ekonomi Mikroskil, 2023)
Indonesia is a country that has many provinces so that goods delivery services are needed by the community and organizations to distribute goods between cities. Seeing the many companies in the field of freight forwarding services, every company competes in providing its best service in order to get the attention of the public, including one of which is PT Pos Indonesia Cimahi Branch Office. This study aims to analyze the effect of corporate image and service quality on customer satisfaction at PT Pos Indonesia Cimahi Branch Office. The method in this research is descriptive and verification with a quantitative approach. The research sample was drawn based on probability sampling with random sampling with a total sample of 100 people and data analysis techniques using the classical assumption test, multiple linear regression analysis, multiple correlation analysis, and analysis of the coefficient of determination. The result of the coefficient of determination (R Square) obtained is 0.739. From the value of the coefficient of determination, it is known that the influence of corporate image and service quality on customer satisfaction is 73.9%, then the remaining 26.1% is influenced by other factors not examined. Suggestions for continuing research that aims to find out other variables that play a role in realizing customer satisfaction, should be expanded by adding other variables such as information quality and customer trust.